Efficacy of air heat exchanger based decay heat removal system through passive mode: A numerical study. (2020) - Elton, D.N.; Arunachala, U.C.; Dolfred, V.F.
Abstract: In nuclear power plant, as the core temperature increases exponentially during pump failure/plant shutdown, there must be an efficient decay heat removal mechanism so as to avoid severe accidents. In this scenario natural circulation loops find its importance as it is a passive heat transport mechanism with no moving parts. Further, based on the application, the single loop may be extended to coupled loop in which the final loop is cooled by an infinite sink which can be atmosphere or ocean. In case of atmosphere-based loop, fins are must as the coolant is air. Hence, in the present study, fin optimization as applicable to natural convection has been done in phased manner through numerical analysis. Initial study indicated better performance by square fin over circular type. Therefore, with this geometry the best fin spacing was finalized as 7 mm based on flow pattern. Further, fin height was optimized both in symmetrical and asymmetrical fashion. As there is a trade-off between heat transfer and frictional force for every case, the best configuration was selected by defining performance evaluation criteria. It resulted in lowest fin height at the bottom and highest at the top as the best case due to better draught effect.